Ethnomathematics in Traditional Weaving: The Potential for Contextualizing Geometry Material in Elementary School Learning in West Papua - Jaizul, Alim; Putra, Deva (International Journal of Ethno-Sciences and Education Research, 2025)
The study, entitled "Ethnomathematics in Traditional Weaving: The Potential for Contextualizing Geometry Material in Elementary School Learning in West Papua," aims to explore the potential of local wisdom in the form of traditional Papuan woven motifs as a source for learning geometry in elementary schools. Using an ethnographic approach, researchers documented geometric elements such as symmetry, transformation, and plane shapes in typical motifs such as Tifa zigzags, diamond lattices, spiral ribbons, and arrows. The analysis results show that the woven patterns are rich in triangles, rectangles, trapezoids, parallelograms, and rhombuses with structured reflection, rotation, and translation transformations. Simulations of calculating the area of the motifs provide concrete examples of how geometric concepts can be integrated into student worksheets based on cultural contexts. The responses of elementary school teachers in Manokwari and Fakfak reinforce the finding that mathematics learning that links local motifs is easier for students to understand, while also fostering pride in cultural identity. This approach is in line with the Independent Curriculum, which emphasizes differentiated and local project-based learning. Theoretically, this research supports the ethnomathematics movement as a strategy for decolonizing mathematics education by positioning local knowledge as a legitimate and contextual learning resource. Thus, the application of ethnomathematics elements to Papuan woven motifs not only enriches pedagogical strategies but also serves as a means of cultural preservation in the modern era. This research recommends the development of teaching modules, teacher training, and the integration of local content into Lesson Plans (RPPs) to encourage sustainable implementation in the classroom.